Small molecule MMRi62 targets MDM4 for degradation and induces leukemic cell apoptosis regardless of p53 status - Lama, Rati; Xu, Chao; Galster, Samuel L.; Querol-García, Javier; Portwood, Scott; Mavis, Cory K.; Ruiz, Federico M.; Martin, Diana; Wu, Jin; Giorgi, Marianna C.; Bargonetti, Jill; Wang, Eunice S.; et al. (Frontiers in Oncology, 2022)
MDM2 and MDM4 proteins are key negative regulators of tumor suppressor p53. MDM2 and MDM4 interact via their RING domains and form a heterodimer polyubiquitin E3 ligase essential for p53 degradation. MDM4 also forms heterodimer E3 ligases with MDM2 isoforms that lack p53-binding domains, which regulate p53 and MDM4 stability. We are working to identify small molecule inhibitors targeting the RING domain of MDM2-MDM4 (MMRi) that can inactivate the total oncogenic activity of MDM2-MDM4 heterodimers. Here, we describe the identification and characterization of MMRi62 as a MDM4-degrader and apoptosis inducer in leukemia cells. Biochemically, MMRi62 binds to preformed RING domain heterodimers, alters the substrate preference toward MDM4 ubiquitination, and promotes MDM2-dependent MDM4 degradation in cells. This MDM4-degrader activity of MMRi62 was found to be associated with potent apoptosis induction in leukemia cells. Interestingly, MMRi62 effectively induced apoptosis in p53 mutant, multi-drug-resistant leukemia cells and patient samples in addition to p53 wild-type cells. In contrast, MMRi67 as a RING heterodimer disruptor and an enzymatic inhibitor of the MDM2-MDM4 E3 complex lacked MDM4-degrader activity and failed to induce apoptosis in these cells. In summary, this study identifies MMRi62 as a novel MDM2-MDM4-targeting agent and suggests that small molecules capable of promoting MDM4 degradation may be a viable new approach to killing leukemia cells bearing non-functional p53 by apoptosis.